JADAL DALAM PANDANGAN AL-QUR’AN DAN PENDIDIKAN KONSELING - Hamdani Khaerul Fikri (el-'Umdah, 2019)
he Qur'an is the Holy Book that contains a clear and detailed truth that span all aspects started to appear. Its existence will never change. The Qur'an is the normative-theoretical guidelines for the implementation of Islamic education that require further interpretation for operations further Islamic education. The content of the Qur'an covers all human dimension and is able to touch the whole human potential, be it in the field of guidance and counselling was given to humans to solve problems encountered in this life. In proving the truth and break the argument people who challenged him, the Qur'an uses the so-called jadal. In the Indonesia language usage defined by the debate. The debate is a dialogue, discussion, to solving problems, a method of debate can be used in the educational world, especially Islamic education and guidance counseling, especially in the application of counseling. Jadal is the exchange of thoughts or opinions with theway each attempted to argue in order to win a thought or opinion in a debate. The various notions of limit Jadal formulated the scholars' but basically refers to the debate as well as the effort showed the truth or defend the truth that ditujunyawith a variety of arguments. Key words: Jadal, Al-Quran, Education And Counseling